The Concept of Subordination as an Element of Employment for Digital Platform Workers in the Republic of Lithuania - Globytė Rūta (Baltic Journal of Law & Politics, 2024)
This research analyzes one element – subordination – of employment relations indicated by the case law of the Republic of Lithuania according to which a civil relationship can be understood as an employment relationship. The elements by which independent contractors (self-employed persons) can be considered employees are established in the case law of the Republic of Lithuania but have never been analyzed in the context of platform workers. Therefore, first, the nature and features of the digital platform and the platform worker are analyzed. Second, the definition of subordination is considered in light of the distinction between employment and civil relations. Third, subordination is analyzed vis-a-vis the relations between the platform and the platform worker (independent contractor) and in light of proposed legal acts for platform workers.